MINIX4RT: a real-time operating system based on MINIX - Pessolani, Pablo Andrés (2006)
Tanenbaum's MINIX Operating System was extended with a Real-Time microkernel and services to conform MINIX4RT, a Real-Time Operating System for academic uses that includes more flexible Interprocess Communications facilities supporting basic priority inheritance protocol, a fixed priority scheduler, timer and event driven interrupt management, statistics and Real-Time metrics gathering keeping backward compatibility with standard MINIX versions.